Complications of laparoscopic surgery in general surgical practice and their management - Doddamani, Rajalaxmi; Hiremath, Srikantaiah Chandrasekharaiah; Ahmed, Zameer; Surapaneni, Lahari (International Surgery Journal, 2018)
Background: Any new technique is associated with the development of new complication. Laparoscopic surgery has gained popularity over last 20 years, owing to many advantages for patients in terms of smaller scar, less post-operative pain and quicker recovery. Despite the relative safety of laparoscopic techniques, inadvertent serious injuries to bowel, bladder and vascular structures do occur. Therefore, the need has arisen to study the various complications and their management inherent in this technique. The objective was to determine percentage of complications in laparoscopic surgeries of abdomen and also to study their management. Methods: Inpatients of Ramaiah hospitals undergoing abdominal laparoscopic surgeries from October 2014 to October 2015 who are above 14 years of age and undergoing elective or emergency surgeries or diagnostic laparoscopy for acute/chronic appendicitis, cholelithiasis and inguinal hernia repair. Demographic information, clinical findings, intra operative and postoperative findings will be noted. Follow up of the patient is done for 4 weeks. Results: Out of the 272, 134(49.3%) were male patients and 138 (50.7%) were female patients, age group ranging between 31-40 years. Four patients (1.4%) showed CBD injury, three patients (1.1%) showed bowel injury, twelve (4.4%) showed bile leak, all these 9 (3.3%) patients were managed by converting the laparoscopic cholecystectomy into open cholecystectomy. Sixteen patients (5.9%) had laparoscopy converted into open procedure due to the intraoperative complications. Statistically significant impact was noted on the outcome of surgery due the complication that patient underwent during the study. Conclusions: Laparoscopy is a safe, effective and well tolerated procedure if conducted in the skilled and experienced hands. The morbidity and mortality are dependent on age, general condition, presence/ absence of comorbidities and hence preoperative thorough work up is imperative. Large proportions of these complications occur during the initial learning curve of the inexperienced laparoscopic surgeon.